Ticks, rickettsial and erlichial infection in small mammals from Atlantic forest remnants in northeastern Brazil. Issue 3 (December 2018) - Lopes, Marcos G.; Muñoz-Leal, Sebastián; de Lima, Julia T. Ribeiro; Fournier, Gislene Fatima da S. Rocha; Acosta, Igor da Cunha L.; Martins, Thiago F.; Ramirez, Diego G.; Gennari, Solange M.; Labruna, Marcelo B.
Abstract: We evaluated infection by Rickettsia spp. and Ehrlichia spp in small mammals and their ticks from two Atlantic forest conservation areas in the state of Rio Grande do Norte, northeastern Brazil. A total of 39 small mammals were captured during 2012–2013, encompassing 33 marsupials (29 Didelphis albiventris, four Monodelphis domestica ), three Cricetidae rodents (two Necromys lasiurus, one Rattus rattus ), one Caviomorpha rodent ( Thrichomys apereoides ) and two armadillos ( Euphractus sexcinctus ). The ticks Amblyomma auricularium, Ixodes loricatus, and Ornithodoros mimon were collected from D. albiventris, whereas only A. auricularium was collected from armadillos. Through immunofluorescence assay with Rickettsia spp. antigens, 6/28 (21%) D. albiventris and the single R. rattus specimen reacted to at least one rickettsial antigen, with highest seroprevalence and endpoint titers to Rickettsia amblyommatis. A total of 150 ticks (126 A . auricularium, nine I. loricatus, 15 O. mimon ) was tested for rickettsial infection by PCR, which detected only R. amblyommatis in most of the A. auricularium ticks. Lung and spleen samples were collected from small mammals (two N. lasiurus, six D. albiventris, three M. domestica, one T. apereoides, one R. rattus ) and were tested by PCR for Anaplasmataceae agents. The spleen from one D. albiventris contained a new ehrlichial agent, here named as Ehrlichia sp. strain Natal. Phylogenetic analysis inferred from the dsb gene of Ehrlichia spp. indicates that this novel agent is potentially a new species. Future studies should monitor the possible role of rickettsial and/or ehrlichial microorganisms as agents of emerging diseases in these degraded areas of Atlantic forest, just as has occurred with other agents in degraded areas of this biome in southeastern Brazil. Graphical abstract: Image 1 Highlights: Amblyomma auricularium, Ixodes loricatus and Ornithodoros mimon ticks were found. Infection by Rickettsia amblyommatis was detected in A. auricularium ticks. Wild small mammals presented serological evidence of R. amblyommatis infection. A potentially novel Ehrlichia species infected the opossum Didelphis albiventris.